Contributions to leg stiffness in high- compared with low-arched athletes - Powell, D. W.; Paquette, M. R.; Williams, D. S. B. 3rd. (Medicine & Science in Sports & Exercise, 2017)
PURPOSE: High-arched (HA) athletes exhibit greater lower extremity stiffness during functional tasks than low-arched (LA) athletes. The contributions of skeletal and muscular structures to stiffness may underlie the distinct injury patterns observed in these athletes. The purpose of this study was to compare skeletal and muscular contributions to leg stiffness in HA and LA athletes during running and landing tasks.